1999
DOI: 10.1103/physrevb.59.9447
|View full text |Cite
|
Sign up to set email alerts
|

Two-magnon processes and ferrimagnetic linewidth calculation in manganese ferrite

Abstract: A procedure has been developed to obtain the two-magnon linewidth contributions in single and polycrystalline ferrites in which, working with ferrimagnetic resonance experiments, the applied field was only slightly larger than the value required to saturate the sample. This theory has been shown to work in manganese ferrites. Single-crystal MnFe 2 O 4 has been prepared by the floating-zone technique and polycrystalline ferrite by the ceramic method. The spinel structure and composition have been confirmed by x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The most typical crystal structures that exhibit three-dimensional geometric and magnetic frustration are spinels and pyrochlores. For several pyrochlores and spinels (R 2 Mo 2 O 7 [3]: R ¼ Sm, Gd and Tb, R 2 Nb 2 O 7 : R ¼ Sm, Gd, Tb, Dy, Ho, Er, Yb, Lu and Y, Tb 2 Ti 2 O 7 [4], MgAl 2 O 4 [5], NiAl 2 O 4 [6], NiFe 2 O 4 [7], MnFe 2 O 4 [8]), single crystals have been obtained by the float-zone (FZ) method. The FZ method has been known as one of the typical single crystal growth method for oxides with relatively high melting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The most typical crystal structures that exhibit three-dimensional geometric and magnetic frustration are spinels and pyrochlores. For several pyrochlores and spinels (R 2 Mo 2 O 7 [3]: R ¼ Sm, Gd and Tb, R 2 Nb 2 O 7 : R ¼ Sm, Gd, Tb, Dy, Ho, Er, Yb, Lu and Y, Tb 2 Ti 2 O 7 [4], MgAl 2 O 4 [5], NiAl 2 O 4 [6], NiFe 2 O 4 [7], MnFe 2 O 4 [8]), single crystals have been obtained by the float-zone (FZ) method. The FZ method has been known as one of the typical single crystal growth method for oxides with relatively high melting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This disorder has caused some confusion both in the analysis of the dependence of magnetic properties on sample size [4][5][6][7] and in understanding the temperature dependence of transport quantities. 12 There, we found that the electronic structure is highly sensitive to the structural parameters used, particularly, the internal O coordinate u of the spinel structure.…”
mentioning
confidence: 99%
“…Kasuya-Le Craw and rapidly relaxing impurities processes have also been omitted. 11 The expression for surface pit contribution is given as 10…”
Section: Methodsmentioning
confidence: 99%